Short-Term Effect on Intraocular Pressure after Intravitreal Aflibercept Injection for Diabetic Macular Edema - Afnan A., Alshehri; Tariq S., Alshehri (International Journal of Innovative Research in Medical Science, 2017)
Purpose: There is limited data available on the short-term effect of intravitreal aflibercept injection on intraocular pressure (IOP) for diabetic macular edema (DME). We performed a prospective, observational clinical study to evaluate short-term IOP changes after aflibercept injection in eyes with DME. Methods: Patients with diabetes mellitus type II and associated DME were recruited at King Abdulaziz Medical City, Saudi Arabia, between December 2015 and October 2016. All eyes were injected with 2 mg(0.05ml) of intravitreal aflibercept. Inclusion criteria were patients with DME, patients eligible for aflibercept injection, patients aged 18 years or more. Exclusion criteria were patients with a history of anti-VEGF injection, argon laser photocoagulation, glaucoma, antiglaucoma medications, uveitis, or steroid. We measured IOP using Tono-Pen (Tono-Pen XL, Reichert Inc., Depew, NY, USA) immediately before injection, at 5, 15, 30, 45, 60 min and 1 day after injection. We compared short-term IOP changes before and after aflibercept injections using paired t-test for statistical analysis. Results: A total of 14 eyes from 14 DME patients (7 female and 7 male) with a mean age of 62.43±10.68 years fulfilled the inclusion criteria. Our findings showed that the mean IOP readings recorded before injection, at 5, 15, 30, 45, 60 min and 1 day after injection were 19.71±1.90, 32.07±13.68 mmHg (p=0.005), 23.43±6.38 mmHg(p=0.043), 20.86±5.07 mmHg(p=0.476),19.50±3.11 mmHg(p=0.803),19.21±3.17 mmHg(p=0.583) and 17.71±1.59(p= 0.011) respectively. Comparing the mean IOP before and after intravitreal aflibercept injection, it was significantly higher at 5 and 15 min after injection. However, the mean IOP returned to normal pre-injection level at 60 min (p=0.583). Three eyes (21.43%) had persistent increased IOP one day after intravitreal aflibercept injection. Comparing pre and post injection mean IOP at 5, 15 min and 1 day in terms of gender effect, the mean IOP changes were not statistically significant (p=0.591, 0.473, 0.345; respectively). Conclusions: Our study confirmed that intravitreal aflibercept injection is safe with respect to short-term IOP changes in patients with DME. A significant short-term rise of IOP occurred within 15 minutes after injection then it returned to normal in most patients. The effect of gender on the mean IOP before and after aflibercept injection was not statistically significant. Keywords: Aflibercept, intraocular pressure, intravitreal injection.